Near‐Infrared Luminescent Ternary Ag3SbS3 Quantum Dots by in situ Conversion of Ag Nanocrystals with Sb(C9H19COOS)3. Issue 70 (26th November 2018) - Di, Qiumei; Wang, Juwen; Zhao, Zhengjing; Liu, Jiajia; Xu, Meng; Liu, Jia; Rong, Hongpan; Chen, Wenxing; Zhang, Jiatao
Abstract: Differently from the normal three single precursor method to produce colloidal ternary quantum dots (QDs), herein ternary Ag3 SbS3 quantum dots (QDs) with efficient near‐infrared (NIR) luminescence have been prepared by a new facile in situ conversion of Ag nanocrystals (NCs) with a binary Sb/S organic precursor Sb(C9 H19 COOS)3 under low temperature. The unprecedented construction evolution from Ag NCs to Ag3 SbS3 /Ag hetero‐structure and final monodisperse Ag3 SbS3 QDs has been demonstrated. These novel Ag3 SbS3 QDs exhibit efficient NIR emission at ≈1263 nm and possess high colloidal stability. Abstract : Hi ho silver : Novel ternary Ag3 SbS3 QDs with efficient NIR luminescence have been prepared by a new facile in situ conversion of Ag NCs with binary Sb/S organic precursor Sb(C9 H19 COOS)3 under low temperature. Gradual in situ conversion from Ag NCs to Ag3 SbS3 /Ag hetero‐structure and final monodisperse Ag3 SbS3 QDs has been demonstrated. The novel Ag3 SbS3 QDs exhibit efficient NIR emission at about 1263 nm and possess high colloidal stability.